2002
DOI: 10.1037/0022-0663.94.2.428
|View full text |Cite
|
Sign up to set email alerts
|

Animated pedagogical agents in multimedia educational environments: Effects of agent properties, picture features and redundancy.

Abstract: Two experiments explored the integration of animated agents into multimedia environments in the context of R. E. Mayer's (2001) cognitive theory of multimedia learning. Experiment 1 was a 3 (agent properties: agent only, agent with gesture, no agent) ϫ 3 (picture features: static picture, sudden onset, animation) design. Agent properties produced no significant effects. Both sudden onset and animation conditions facilitated performance relative to the static-picture condition. In Experiment 2, we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(178 citation statements)
references
References 26 publications
10
165
0
3
Order By: Relevance
“…Several different cueing techniques for pointing out crucial connections between representations in various studies, like flashing to connect related elements (Craig et al 2002;Jeung et al 1997), giving related elements the same color (Kalyuga et al 1999), and orienting cues (i.e., gestures, gaze) as guides to related elements (Lusk and Atkinson 2007), showed that cueing improves the retention for cued content and facilitates the application of learned information as reflected in better performances on problem-solving transfer tasks or reduced problem-solving time. However, the positive effects of relational cues on transfer performance are not always found (Jamet et al 2008;Tabbers et al 2004), suggesting that the effects of cueing on deep comprehension (i.e., transfer) are less consistent.…”
Section: Relating Elements Between Representationsmentioning
confidence: 99%
“…Several different cueing techniques for pointing out crucial connections between representations in various studies, like flashing to connect related elements (Craig et al 2002;Jeung et al 1997), giving related elements the same color (Kalyuga et al 1999), and orienting cues (i.e., gestures, gaze) as guides to related elements (Lusk and Atkinson 2007), showed that cueing improves the retention for cued content and facilitates the application of learned information as reflected in better performances on problem-solving transfer tasks or reduced problem-solving time. However, the positive effects of relational cues on transfer performance are not always found (Jamet et al 2008;Tabbers et al 2004), suggesting that the effects of cueing on deep comprehension (i.e., transfer) are less consistent.…”
Section: Relating Elements Between Representationsmentioning
confidence: 99%
“…A diagram and text that redescribes the diagram provides an obvious example as does presenting the same material in written and spoken form. The redundancy effect is demonstrated when eliminating the redundant material improves learning (see Cerpa, Chandler and Sweller 1996;Sweller 1991, 1996;Craig, Gholson and Driscoll 2002;Kalyuga, Chandler and Sweller 1999;Mayer, Heiser and Lonn 2001;Mayer, Bove, Bryman, Mars and Tapangco 1996;Anderson 1980, 1982;Sweller and Chandler 1994).…”
Section: Cognitive Load Theorymentioning
confidence: 99%
“…They consist of the aspects of the visual and auditory presence of the APA that are hypothesized to ''make the learning experience more interesting, believable, or natural'' (p. 508). Empirical studies of these properties have explored the influence of the APA's age, gender, ethnicity, politeness, responsiveness, dynamism, and visual appeal, among others (e.g., André et al 1996;Arroyo et al 2011Arroyo et al , 2009Baylor 2011;Baylor and Kim 2004;Baylor and Ryu 2003;Craig et al 2002;Domagk 2010;Kim et al 2007;Lester et al 1997;Moreno 2004;Moreno et al 2000;Plant et al 2009;Wang et al 2008;Woolf et al 2010). Given our special interest in gender and science education, we summarize below the empirical studies that have investigated gender and motivation in relation to APAs in virtual science learning environments.…”
Section: Animated Pedagogical Agents and Student Motivationmentioning
confidence: 99%